THE CORRELATION BETWEEN JAVANESE CULTURE AND EMPLOYEE ENGAGEMENT: A SYSTEMATIC LITERATURE REVIEW - Haryanto Haryanto; Amelia Setiawan (SEAN Institute, 2023)
In today's digital age, companies are shifting towards digital-based business models where employees have the flexibility to work remotely from their homes. As a result, employee engagement has become a crucial topic of discussion. The quality of employee engagement directly impacts employee performance and the success of the company. Javanese culture is a prevalent culture in Indonesia and is commonly adopted by companies in the region. This research aims to analyze the influence of Javanese culture on employee engagement through a systematic literature review of articles published on the Google Scholar database between 2000-2021. The study finds that Javanese culture, with its teachings of mutual respect, modesty, teamwork, and responsibility, is easily accepted by employees. These values foster trust and ultimately increase employee engagement. Additionally, the power dynamics within Javanese culture can positively or negatively affect employee engagement, depending on the level of autonomy granted by leaders to subordinates.